Adoption of BIM by architectural firms in India: technology–organization–environment perspective. (3rd July 2016) - Ahuja, Ritu; Jain, Megha; Sawhney, Anil; Arif, Mohammed
ABSTRACT: Building information modelling (BIM) is being heralded as a remarkable innovation in the built environment sector with expectations of lofty sector-wide improvements. Some countries have shown remarkable levels of uptake of BIM, along the way documenting some evidence of benefits stemming from BIM. However, countries such as India and China are late entrants in the BIM adoption journey and are seeing a slower adoption rate. This study develops a model using the technology–organization–environment framework to study the factors influencing BIM adoption by architectural firms in India and reasons for this slow adoption. The proposed model of BIM adoption is tested using the partial least square method against responses collected from 184 industry professionals based in India. Findings reveal that the adoption of BIM by Indian architectural firms is at the 'experimentation' stage with variables such as expertise, trialability, and management support exhibiting a strong positive influence on BIM adoption. The study also explains the status of BIM adoption in India with the help of a multi-level social construct, which places the level of BIM adoption in India between the micro- and meso-levels of organizational scales. Similarities and dissimilarities with previous findings are discussed in the paper to highlight the findings of this study.